Leaf functional traits vary within and across tree species in tropical cloud forest on rock outcrop versus volcanic soil. (13th November 2019) - Vergara‐Gómez, Diana; Williams‐Linera, Guadalupe; Casanoves, Fernando
Abstract: Question: Functional leaf traits are used to classify plants into ecological strategies according to the leaf economic spectrum. Geological substrate has an important effect on functional trait variation; however, interspecific and intraspecific trait variation on contrasting substrates needs to be documented for tropical humid forests. We hypothesized that a conservative resource strategy is prevalent in forests on rocky outcrops (FOR) and an acquisitive strategy is prevalent in forests on volcanic substrate (FOV). Our aim was to determine interspecific and intraspecific variation in functional traits of tree species on FOR and FOV. Location: Tropical cloud forests on limestone outcrops and deep volcanic soil close to each other, Veracruz, Mexico. Methods: At four sites in FOR and four sites in FOV, we selected 16 native tree species: five occurring only in FOR, five occurring only in FOV, six common to both. We determined leaf area (LA), specific leaf area (SLA), stomatal density (SD), and foliar C, N and P content. Functional trait differences between FOR and FOV were determined using linear mixed models. Results: Leaf traits differed between substrates and interspecifically. LA, SLA and foliar C content were higher in FOV than in FOR. Tree species common to both substrates displayed significant substrate × species interaction, but LA, SLA, SD and foliar C showed different trends in each substrate. Our results indicate that tree species on different substrates within the same vegetation type display different functional strategies. Conclusions: Leaf trait variation supports the hypothesis that tree species use strategies congruent with resource conservation in FOR and resource acquisition in FOV. Intraspecific variation of LA, SLA and SD in tree species growing on both substrates suggests plasticity to adapt locally to changes in substrate conditions. LA and SLA are critical indicator traits of the use and allocation of resources in FOR and FOV. Abstract : We investigated leaf trait variation within and across tree species growing on rocky outcrops (FOR) and on deep volcanic soil (FOV) in a tropical cloud forest. Resource conservation strategies prevailed in FOR and resource acquisition strategies in FOV. Leaf area and specific leaf area are critical indicator traits for the use and allocation of resources in FOR and FOV (Photograph: Diana Vergara).